A critical analysis of the notary supervision implementation: A study in three cities in central Java province and Yogyakarta special region, Indonesia - Prakoso, Andria Luhur; Dimyati, Khudzaifah; Absori; Wardiono, Kelik; Budiono, Arief (International Journal of Innovative Research and Scientific Studies, 2025)
Notaries have a crucial role in legal relations in society as they create deeds that can provide legal certainty and simultaneously prevent future disputes. There is a need for supervision to prevent notaries from committing reprehensible actions and to maintain the dignity of the profession in Indonesia. This aims to analyze the Local Supervisory Council’s implementation of notary supervision, the problems that occur in its implementation, and how to resolve them. This study employed an empirical legal paradigm, meaning that the primary data were collected from interviews with selected sources. The object studied was the implementation of notary supervision by the Local Supervisory Council. The location of this study was the working area of Local Supervisory Councils in Central Java Province, encompassing Sukoharjo Regency, Yogyakarta City, and Semarang City. Results showed that there were two patterns of supervision, namely reactive supervision and proactive supervision. Concerning the problems in its implementation, the Local Supervisory Council was found to have failed to carry out its obligations to store notary protocols. Apart from that, based on the notary office law, there is an overlap of authorities between the two institutions in conducting coaching activities. This paper encourages better supervision of notaries by the Local Supervisory Council, as it was shown that it is crucial to properly carry out supervision. There must be efforts to amend the notary office law to prevent the overlap of authorities and create regulations that support the storage of notary protocols.